Efektivitas Penggunaan Media Pembelajaran Interaktif dalam Pembelajaran Matematika di Sekolah Dasar - Nisa Maghfiroh, Alifia; Muhammad Ferelian El Hilaly Daksana; Nikhlatus Salma, Siti (Griya Journal of Mathematics Education and Application, 2024)
This study investigates the impact of using interactive learning media, particularly colorful markers, on mathematics learning in elementary schools. Focusing on SDN 1 and SDN 2 Slamet in Tumpang sub-district, Malang district, the study aimed to evaluate the effectiveness of color markers in improving students' understanding of mathematical concepts, learning interest and test results. A survey research method was used by collecting data through student questionnaires and analysis of test results. The survey results showed significant differences between students who used interactive learning media of color markers and students who used conventional media. Students who engaged in interactive learning showed higher learning interest and better test results. Students' enthusiasm and engagement in learning increased, creating a dynamic learning environment. The improvement in test results also signifies the effectiveness of interactive learning media in communicating mathematical concepts. The conclusion of this study emphasizes that the use of colorful markers not only contributes positively to the understanding of mathematical concepts, but also positively affects students' motivation and participation. The implication is that the choice of appropriate and attractive learning media can shape students' perception of mathematics as an interesting and fun subject at the primary level.